Penerapan Pupuk Urea pada Tumpangsari Jagung â€œDouble Rowâ€ dan Kacang Tanah Terhadap Pertumbuhan dan Hasil Jagung (Zea mays L.) - Gadmor, Margaretha S.; Nurmauli, Niar; Timotiwu, Paul B.; Hamim, Herawati (Jurnal Penelitian Pertanian Terapan, 2017)
The study aims to determine: (1) response growth and result of corn and peanut on monoculture and intercropping; (2) an optimal urea doze on growth and result of corn and peanut. Research did from July to November 2014 in Laboratory of Integrated, Faculty of Agriculture, University of Lampung. The research used complete Random Group Design with Triple Multiply. Homogenity of variance was tested by Bartlett test. Separation of median is done by using the test Polynomial Orthogonal with real level 5 %. The result showed that picking of corn per hectar for monoculture higher than intercropping but the other variable wasn?t really different. Peanut monoculture higher than intercropping for number of pods, weight of 100 grains, and production of seed per hectar but for plant height and greening level, pattern levels of intercropping higher than monoculture, and there were not find an optimal urea doze for corn on intercropping of corn ?double row? and peanut. Keywords : corn, intercropping, peanuts, urea